Occurrence and distribution pattern of acidic pharmaceuticals in surface water, wastewater, and sediment of the Msunduzi River, Kwazulu‐Natal, South Africa. (3rd December 2015) - Agunbiade, Foluso O.; Moodley, Brenda
Abstract: The paucity of information on the occurrence of pharmaceuticals in the environment in African countries led the authors to investigate 8 acidic pharmaceuticals (4 antipyretics, 3 antibiotics, and 1 lipid regulator) in wastewater, surface water, and sediments from the Msunduzi River in the province of KwaZulu‐Natal, South Africa, using solid‐phase extraction (SPE) and liquid chromatography–mass spectrometry (LC/MS). The method recoveries, limits of detection (LOD), and limits of quantification were determined. The method recoveries were 58.4% to 103%, and the LODs ranged between 1.16 ng/L and 29.1 ng/L for water and between 0.58 ng/g and 14.5 ng/g for sediment. The drugs were all present in wastewater and in most of the surface water and sediment samples. Aspirin was the most abundant pharmaceutical observed, 118 ± 0.82 μg/L in wastewater influent, and the most observed antibiotic was nalidixic acid (25.2–29.9 μg/L in wastewater); bezafibrate was the least observed. The distribution pattern of the antipyretic in water indicates more impact in suburban sites. The solid–liquid partitioning of the pharmaceuticals between sediment and water, measured as the distribution coefficient (log  K D ) gave an average accumulation magnitude of 10× to 32× in sediments than in water. The downstream distribution patterns for both water and sediment indicate discharge contributions from wastewater, agricultural activities, domestic waste disposal, and possible sewer system leakages. Although concentrations of the pharmaceuticals were comparable with those obtained from some other countries, the contamination of the present study site with pharmaceuticals has been over time and continues at present, making effective management and control necessary. Environ Toxicol Chem 2016;35:36–46. © 2015 SETAC